Robust relation between temporal discounting rates and body mass - Jarmolowicz, David P.; Cherry, J.Bradley C.; Reed, Derek D.; Bruce, Jared M.; Crespi, John M.; Lusk, Jayson L.; Bruce, Amanda S. (My University, 2014)
When given the choice between $100 today and $110 in 1 week, certain people are more likely to choose the immediate, yet smaller reward. The present study examined the relations between temporal discounting rate and body mass while accounting for important demographic variables, depressive symptoms, and behavioral inhibition and approach. After having their heights and weights measured, 100 healthy adults completed the Monetary Choice Questionnaire, the Beck Depression Inventory-II, and the Behavioral Inhibition Scale/Behavioral Approach Scale. Overweight and obese participants exhibited higher temporal discounting rates than underweight and healthy weight participants. Temporal discounting rates decreased as the magnitude of the delayed reward increased, even when other variables known to impact temporal discounting rate (i.e., age, education level, and annual household income) were used as covariates. A higher body mass was strongly related to choosing a more immediate monetary reward. Additional research is needed to determine whether consideration-of-future-consequences interventions, or perhaps cognitive control interventions, could be effective in obesity intervention or prevention programs.
Keywords: Delay discounting; Delayed gratification; Depression; Impulsivity; Risk factors; Obesity